MAPING AND MONITORING FOR THE VALUATION OF SOIL FUNGI AND CHILI DAMPING OFF - M. Ali; A. A. Shahid; M. N. Subhani (Journal of Animal and Plant Sciences, 2019)
Capsicum annum is one of the most important spice crop of Pakistan which is threatened by damping off which is soil borne nursery disease and responsible for more than 70% losses in the yield. A systematic survey in chili field of Lahore District was conducted to estimate the incidence, prevalence and % mortality of the seedlings due to damping off disease. Another important objective of the research was to design a map for the distribution of this disease in Lahore. 15 villages around the main city of Lahore were visited for sampling and data recording. Maximum disease incidence (47%) was observed in the village Shamkibhattian while the minimum disease incidence (09%) was recorded in the village Chappa. For the disease prevalence and percentage mortality the maximum values were 100% and 39% while the minimum values were 67% and 4% respectively. A detailed map of the district was also designed highlighting the distribution of chili damping off in the Lahore. Population dynamics as well as percentage frequency of soil borne oomycetes and other fungi were calculated. Species of Pythium, Aspergillus and Mucor were among the frequently isolated species. The main objective of the following research is to map the damping off disease in Lahore district as well as to estimate the level of pathogenic population and disease incidence.
Keywords: Capsicum annum; Chili; Damping off; Soil borne disease; Disease incidence; Prevalence; Percentage mortality; Lahore District; Disease mapping; Population dynamics; Pythium; Aspergillus; Mucor; Seedling mortality; Oomycetes